2016
DOI: 10.1002/14651858.cd011389.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open gastrectomy for gastric cancer

Abstract: Based on low quality evidence, there is no difference in short-term mortality between laparoscopic and open gastrectomy. Based on very low quality evidence, there is no evidence for any differences in short-term or long-term outcomes between laparoscopic and open gastrectomy. However, the data are sparse, and the confidence intervals were wide, suggesting that significant benefits or harms of laparoscopic gastrectomy cannot be ruled out. Several trials are currently being conducted and interim results of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 66 publications
6
62
0
11
Order By: Relevance
“…Some literature concluded that LADG was associated with a lower postoperative complication rate in AGC patients [26, 27]; others found no significant difference between LADG and ODG concerning postoperative morbidity [14, 28]. Even a meta-analysis reported by Cochrane Database considered that the evidence qualities of most completed or ongoing RCTs were low because of high risks of bias [29]. Since operative safety is an essential prerequisite and basis for new surgical procedures, well-designed trials are needed to validate the safety and efficacy of LADG for AGC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Some literature concluded that LADG was associated with a lower postoperative complication rate in AGC patients [26, 27]; others found no significant difference between LADG and ODG concerning postoperative morbidity [14, 28]. Even a meta-analysis reported by Cochrane Database considered that the evidence qualities of most completed or ongoing RCTs were low because of high risks of bias [29]. Since operative safety is an essential prerequisite and basis for new surgical procedures, well-designed trials are needed to validate the safety and efficacy of LADG for AGC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer (GC) is the fourth most common malignant disease and the third leading cause of cancer-related deaths worldwide [1, 2]. Almost 50% of gastric cancer patients are Chinese, many of whom are diagnosed with advanced stage cancer [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported in Cochrane Database of Systematic Reviews that there was no evidence for any differences in short‐term or long‐term outcomes between open and laparoscopic gastrectomy . However, the data are sparse, and the CIs were wide, suggesting that significant benefits or harms of laparoscopic gastrectomy cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews that there was no evidence for any differences in short-term or long-term outcomes between open and laparoscopic gastrectomy. 93 However, the data are sparse, and the CIs were wide, suggesting that significant benefits or harms of laparoscopic gastrectomy cannot be ruled out. With respect to surgical methods used for SLN detection, our subgroup analysis did not found significant differences between open and laparoscopic gastrectomy.…”
Section: It Was Recently Reported In Cochrane Database Of Systematicmentioning
confidence: 99%